Incidence, Aetiology, and Associated Fracture Patterns of Infraorbital Nerve Injuries Following Zygomaticomaxillary Complex Fractures: A Retrospective Analysis of 272 Patients. Issue 2 (June 2022) - Dubron, Kathia; Verbist, Maarten; Shaheen, Eman; Dormaar, Titiaan Jacob; Jacobs, Reinhilde; Politis, Constantinus
Study Design: Retrospective study. Objective: Zygomaticomaxillary complex (ZMC) fractures are common facial injuries with heterogeneity regarding aetiologies, fracture types, infraorbital nerve (ION) involvement, and treatment methods. The aim of this study was to identify associations between aetiologies, fracture types, and neurological complications. Additionally, treatment methods and recovery time were investigated. Methods: Medical files of 272 patients with unilateral and bilateral ZMC fractures were reviewed, whose cases were managed from January 2014 to January 2019 at the Department of Oral and Maxillofacial Surgery, University hospitals Leuven, Belgium. History of ION sensory dysfunction and facial nerve motoric dysfunction were noted during follow-up. Results: ION hypoaesthesia incidence was 37.3%, with the main causes being fall accidents, road traffic accidents, and interpersonal violence. Significant predictors of ION hypoaesthesia were Zingg type B fractures ( P = 0.003), fracture line course through the infraorbital canal ( P < .001), orbital floor fracture ( P < 0.001), and ZMC dislocation or mobility ( P = 0.001). Conclusion: Of all ZMC fractures, 37.3% exhibited ION hypoaesthesia. Only ZMC Zingg type B fractures (74.0%) were significantly more associated with ION hypoaesthesia. ION hypoesthesia was more likely (OR = 2.707) when the fracture line course ran through the infraorbital canal, and was less dependent on the degree of displacement. Neuropathic pain symptoms developed after ZMC fractures in 2.2% patients, posing a treatment challenge. Neuropathic pain symptoms were slightly more common among women, and were associated only with type B or C fractures. No other parameters were found to predict the outcome of this post-traumatic neuropathic pain condition.